GAMBARAN KEBERSIHAN GIGI DAN MULUT PADA REMAJA (STUDI LITERATUR) (Jurnal Kesehatan Siliwangi, 2021)
Dental and oral hygiene is a condition that shows that a person's mouth is free from dirt such as debris, plaque, and tartar. Plaque will always form on the teeth and spread to the entire surface of the teeth if someone ignores dental and oral hygiene. and gingiva often occur in adolescents aged 12-15 years. This study aims to determine how the dental and oral hygiene of adolescents. This type of research is carried out using the literature review method. Literature review is a comprehensive overview of existing research or that has been carried out on a specific topic for what is known or unknown about the topic, as well as to seek rationale and ideas. for further research. Researchers describe dental and oral hygiene obtained from secondary research data Minahasa Regency, at Watampone and at Unaaha Junior High School. The results obtained after reviewing that the criteria for dental and oral hygiene in adolescents on average are moderate. Factors that can affect dental and oral hygiene in adolescents are behavioral and socio-economic factors.